Radiotherapy and Cytokine Storm: Risk and Mechanism - Zhang, Chen; Liang, Zhenzhen; Ma, Shumei; Liu, Xiaodong (Frontiers in Oncology, 2021)
As one of the major methods of cancer treatment, radiotherapy (RT) shows advantages as one of the most important precise therapy strategies. High-dose hypofractionated RT is increasingly widely used in clinical applications due to the protection of local anatomical structure and relatively mild impairment. With the increase of single dose, from 2~20 Gy, and decrease of fractionation, if there is any uniform standard of dose limits for different therapeutic regimens attracts more and more attention, and the potential adverse effects of higher dose radiation have not been elucidated. In this study, the immunological adverse responses induced by radiation, especially the cytokine storm, will be elucidated, which contributes to achieving optimal hypofractionated RT regimen, improving the killing of cancer cells and avoiding the severe side effects.